Sexual dimorphism in immunity across animals: a meta‐analysis. (4th October 2018) - Kelly, Clint D.; Stoehr, Andrew M.; Nunn, Charles; Smyth, Kendra N.; Prokop, Zofia M.
Abstract: In animals, sex differences in immunity are proposed to shape variation in infection prevalence and intensity among individuals in a population, with females typically expected to exhibit superior immunity due to life‐history trade‐offs. We performed a systematic meta‐analysis to investigate the magnitude and direction of sex differences in immunity and to identify factors that shape sex‐biased immunocompetence. In addition to considering taxonomic and methodological effects as moderators, we assessed age‐related effects, which are predicted to occur if sex differences in immunity are due to sex‐specific resource allocation trade‐offs with reproduction. In a meta‐analysis of 584 effects from 124 studies, we found that females exhibit a significantly stronger immune response than do males, but the effect size is relatively small, and became non‐significant after controlling for phylogeny. Female‐biased immunity was more pronounced in adult than immature animals. More recently published studies did not report significantly smaller effect sizes. Among taxonomic and methodological subsets of the data, some of the largest effect sizes were in insects, further supporting previous suggestions that testosterone is not the only potential driver of sex differences in immunity. Our findings challenge the notion of pervasive biases towards female‐biased immunity and the role of testosterone in driving these differences.